Current Practices on Government Innovation towards Human Capital Development for Achieving UAE Vision 2021 - Zayed Hussain Salih ALHEMAIRY; Wan Fauziah Wan YUSOFF (Communications of International Proceedings, 2020)
In any organization, the performance of HC plays an integral role in organization success. Although human capital competencies vary widely, but they are crucial part in the workplace. The development of human capital is one of the pillars of success in most industries. Innovation is one of the elements that have transformed the business in recent decades. UAE has arisen as a country with a resilient awareness and encouraging approach towards innovation. The vision of UAE government is to become one of the most initiative governments by the year 2021. Therefore, this study is designed to analyze the current innovation practices by the government towards human capital development as well as innovation management and examined the direct relationships between these variables. To achieve this goal, quantitative methods were applied after the survey in The Ministry of Community Development (MOCD). The total number of population equal to 1230 individuals. Those individuals represent the staff working in MOCD. The outcome of this study revealed significant relationships between all variables. This research makes the following contributes: first, a valid factor structure for innovation and human capital development was formulated; second, measurement of the influence of these variables in public organizations was validated.
Keywords: Innovation Practices (IP); Human Capital Development (HCD); Innovation Management (IM); Human Capital (HC).